Nutritional analysis of coffee dregs for utilization purposes using classical, ICP-OES and FT-NIR techniques - Kárpáti Zsóka (Élelmiszervizsgálati közlemények, 2018)
Coffee dregs are a byproduct left behind in significant amounts after brewing coffee. Several researches have dealt with its utilization possibilities and have proven, in certain cases, its positive effect. In our study, the applicability of coffee dregs as a soil improver was investigated. The pH, dry matter and water-soluble total salt content of coffee dregs, produced as the byproduct of coffee beverages prepared by the espresso method were determined. The mineral content of the samples was measured using the ICP-OES technique. The FT-NIR spectra of the samples were recorded and pattern recognition was carried out according to growing site and preparation method (French Press and Espresso) by the chemometric evaluation of the spectral data.